HBV, HCV, AND HIV SEROPOSITIVITY: RISKS AND PREVENTION STRATEGIES. : JPUMHS; 2025:15:01,112-118. http://doi.org/10.46536/jpumhs/2025/15.01.604 - Muhammad Bilal1, Shazar Kiani2, Maryam Zahra3, Izzah Rahim4, Haroon ur Rasheed5, Sanum Sultana Khattak6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Serological testing serves as the frontline methodology for the diagnosis of viral infections including hepatitis B virus (HBV), hepatitis C virus (HCV) and human immunodeficiency virus (HIV) infection, especially in cases where direct identification of the pathogen is complicated. OBJECTIVE: Public screening and health monitoring of a population using serological assays are vital from a public health perspective since these tests identify both current and past infections. METHODS: This cross-sectional study diagnosed 150 patients for HBsAg, anti-HCV, and HIV antigen/antibody using rapid serum immunochromatographic lateral flow assays. Each sample was processed using the enclosed instructions, and test lines and control lines’ marking were used to conclude on results interpretation. Stratifications were made based on sex, age, region of residence, and transfusion history. Relations of patient attributes and infection status were studied with Chi-square tests. RESULTS: Within the cohort of 150 patients, the prevalence rates of HBsAg and HCV were 63.3% and 42.0% respectively. There was no statistically significant difference associated with gender for positivity of HBsAg (p = 1.00), HCV (p = 0.60), or HIV (p = 0.36). There were also no age group associations with positivity for any of the infections (HBsAg: p = 0.50; HCV: 0.38; HIV: 0.47). Area of residence was not significantly associated with infection status for HBsAg (p = 0.92), HCV (p = 0.57), or HIV (p = 0.21). A significant association was observed between a history of blood transfusion and HCV positivity (p = 0.023), and borderline association for HIV (p = 0.062); for HBsAg no significant association was noted (p = 0.20). CONCLUSION: The investigation exposed the examined population with concerning levels of HBV and HCV seropositivity alongside notable associations between HCV infection and a history of blood transfusions. The study illustrates the persistent danger of transfusion-related infections and reinforces the need for stringent blood donation protocols, enhanced infection control measures, and intensive epidemiological surveillance. Additional studies with broader scopes, along with deeper analyses into the factors of risk are necessary for designing effective health policy frameworks for prevention and proactive public health responses.